PENERAPAN METODE CAMEL DALAM MENILAI TINGKAT KESEHATAN PT BANK RAKYAT INDONESIA (PERSERO) TBK PERIODE 2023-2025 - Alfaz Syihab Gunawan; Dilla Novi Amelia; Zauzia Siti Zahra; Dede Rohmat; Hani hatimatunnisani (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2026)
This study aims to analyze the financial soundness level of PT Bank Rakyat Indonesia (Persero) Tbk during the 2023–2025 period using the CAMEL method. The CAMEL method evaluates bank soundness based on five main aspects: Capital, Asset Quality, Management, Earnings, and Liquidity. This research employs a descriptive quantitative approach using secondary data obtained from the officially published annual financial statements of Bank BRI. The ratios analyzed include the Capital Adequacy Ratio (CAR), Productive Asset Quality Ratio (KAP), Net Profit Margin (NPM), Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR). The results indicate that, in general, the financial soundness of Bank BRI during the 2023–2025 period is classified as sound, with capital adequacy in a very sound condition. However, aspects related to management performance and operational efficiency still require attention, as reflected by declining profitability ratios and increasing operating expenses. This study is expected to provide useful references for related stakeholders and future research in the banking sector.